Colon Classification for Macro-Documents in Mathematics - Neelameghan, A.; Seetharama, S. (Journal of Information and Knowledge, 1973)
Enumerates the objectives of revision of the Colon Classification (CC) schedule for the classification of subjects going with the Basic Subject "B Mathematics". The methods adopted for implementing the prescriptions of the Law of Parsimony, and for improving the facet structure are briefly discussed. A revised schedule of CC for Mathematics for subjects embodied in Macro-documents, such as a book taken as a whole, is given. An index to the schedule, one hundred and thirty four examples of subjects classified according to the scheme, and an alphabetical index to these subjects, are given.